Leaf morphophysiology of coffee plants under different levels of light restriction - César, Fábio Ricardo Coutinho Fontes; Matsumoto, Sylvana Naomi; Viana, Anselmo Eloy Silveira; Santos, Marcos Antônio Ferreira; Bonfim, Joice Andrade (Coffee Science - ISSN 1984-3909, 2011)
The aim of this study was to evaluate the morphophysiological behavior of coffee leaves (Coffea arabica L.) maintained under different levels of artificial shading in initial vegetative phase. The experiment was carried out from January to June/2007, in agricultural field of Universidade Estadual do Sudoeste da Bahia – UESB, Vitória da Conquista, Bahia, Brazil. Four trials were carried out maintaining shading conditions (30, 50 and 70% of sun light radiance) and at a full sunlight, during 90 days after plantlet emergence. For each assay, Catuaí (IAC144), Catucaí 2SL and Acauã varieties were evaluated, following a randomized block design, considering number of leaves, leaf area, leaf relative water content, leaf water potential, number of ordinary epidermis and stomata cell and stomata index. Shading levels affect the water status of coffee plants, resulting in alterations of morphophysiology of leaves. Increase of leaf water content occurs simultaneously with decrease of modulus of water potential and proline content, denoting an interaction between shading and water content to coffee plants. Higher proline content was verified in Catuaí leaves in comparison to Catucaí variety. With light restriction there was a reduction of ordinary epidermis cell and stomata density. Upward of leaf area and leaf number was observed when the light restriction was similar or lower to 42,86 and 25,0 %, respectively.